Analisis Pengaruh Lingkungan Fisik, Kualitas Pelayanan, dan Kepuasan Terhadap Niat Berkunjung Kembali Pada Resort di Kota Batam - Dewirahayu Sad Wijaya; Ratih Anggraini (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2023)
The tourism and hospitality industry in Indonesia is in recession due to the COVID-19 pandemic. Many businesses have closed to help keep the virus under control, such as shopping malls and tourist attractions. Staycation opportunities in the midst of the COVID-19 pandemic can be a profitable business for tourism stakeholders. Taking advantage of the staycation opportunities has increased the popularity of hotels and resorts in Batam City. The study aims to analyze the influence of the physical environment, service quality, and satisfaction on the intention of revisiting resorts in Batam City. The research uses a quantitative approach by examining various variables and analyzed through the sampling process. The respondents of the study were local and domestic tourists who had stayed in Batam City. The results showed that there was a positive influence between the physical environment, service quality, and satisfaction with the intention to revisit. Resort businesses need to understand the concept of staycation and the importance of improving products, services, and satisfaction to customers so that there is a desire to revisit.